2022
DOI: 10.1007/s11606-021-07230-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Sociodemographic Status Associated with Empathic Communication and Decision Quality in Diabetes Care?

Abstract: Objective To assess the relationship between empathic communication, shared decision-making, and patient sociodemographic factors of income, education, and ethnicity in patients with diabetes. Research Design and Methods This was a cross-sectional study from five primary care practices in the Greater Toronto Area, Ontario, Canada, participating in a randomized controlled trial of a diabetes goal setting and shared decision-making plan. Participants include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The result of the current study indicated that Harvard University had the highest number of publications, centrality, and citations, suggesting that this institution contributed much to applying SEM in nursing research (Carlile et al, 2022;Radwin et al, 2019). University of Toronto published 48 articles with a centrality of 0.10, implying that this institution also played a key role in this field (Bruno et al, 2022;Buckley et al, 2021). Additionally, the overlay visualization mapping indicated that University of Massachusetts and Kyune Hee University have also made contribution in this field in the recent years (Ayotte et al, 2022;S.…”
Section: Discussionmentioning
confidence: 63%
“…The result of the current study indicated that Harvard University had the highest number of publications, centrality, and citations, suggesting that this institution contributed much to applying SEM in nursing research (Carlile et al, 2022;Radwin et al, 2019). University of Toronto published 48 articles with a centrality of 0.10, implying that this institution also played a key role in this field (Bruno et al, 2022;Buckley et al, 2021). Additionally, the overlay visualization mapping indicated that University of Massachusetts and Kyune Hee University have also made contribution in this field in the recent years (Ayotte et al, 2022;S.…”
Section: Discussionmentioning
confidence: 63%